2020
DOI: 10.1002/vzj2.20074
|View full text |Cite
|
Sign up to set email alerts
|

Modeling tomato evapotranspiration and yield responses to salinity using different macroscopic reduction functions

Abstract: Plant responses to salinity can be used to manage irrigation with brackish water. This study evaluated effects of brackish water irrigation on tomato (Solanum lycopersicum L.) plants, proposed a new model to describe plant relative evapotranspiration (ET) and relative yield as a function of electrical conductivity of soil saturated paste extract (EC e), and compared the estimations of the new model with four other models (linear model of Mass and Hoffman, and three nonlinear models of van Genuchten, Dirksen, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…Aboveground plant biomass was lower for RO irrigated trees than the control treatment and that decreased the total ET further. Our results also agreed with other published studies for glycophytes (Baath et al, 2020;Yang et al, 2020) and halophytes (Flores et al, 2016;Katerji et al, 2009;Ozturk et al, 2018), where the plants biomass decreased with increasing salinity with attendant decreases in the ET. Noaman and El-Haddad (2000) also reported decreases in ET with increasing irrigation water salinity ranging between 2 and 6 dS m −1 .…”
Section: Water Balancesupporting
confidence: 93%
See 1 more Smart Citation
“…Aboveground plant biomass was lower for RO irrigated trees than the control treatment and that decreased the total ET further. Our results also agreed with other published studies for glycophytes (Baath et al, 2020;Yang et al, 2020) and halophytes (Flores et al, 2016;Katerji et al, 2009;Ozturk et al, 2018), where the plants biomass decreased with increasing salinity with attendant decreases in the ET. Noaman and El-Haddad (2000) also reported decreases in ET with increasing irrigation water salinity ranging between 2 and 6 dS m −1 .…”
Section: Water Balancesupporting
confidence: 93%
“…They have gotten attention because they depend on soil water content (Cosenza et al, 2003;O'Donnell et al, 2009) and influence the energy partitioning at the soil surface, soil temperature, and the transfer of heat and water across the soil surface (Ochsner et al, 2001). Higher water content is reported in soils irrigated with brackish waters (Yang et al, 2020). According to Modi et al (2013), thermal conductivity was higher when the moisture content was high, and it decreased with decreasing soil moisture content.…”
Section: Core Ideasmentioning
confidence: 99%
“…For instance, Phogat et al [47] suggested that annual gypsum application at a rate of 1.7 t. ha −1 together with a leaching fraction of at least 20% was adequate for managing this soil salinity and sodicity hazard. The calculated soil salinity threshold values for yield decline were 1.73 dS m −1 for EC e and 2.52 dSm −1 [48]. Controversially, in soilless tomato crops, water with electrical conductivity up to 4.0 dS m −1 positively affected photosynthetic rate, crop growth [49] and fruit taste quality characteristics.…”
Section: Water Qualitymentioning
confidence: 94%
“…Irrigation, soil, and plant specialists have interacted ever since to derive strategies to overcome soil and water quality problems from salinity while creating solutions for growers who depend on efficiency and functionality of crop irrigation. Whereas focused on long-term soil salinity dynamics, Yang et al (2020) investigate the potential risk of using brackish water for irrigation, especially with regard to crop yield and effects on evapotranspiration (ET). At the same time, they develop a new model to detect threshold values for the electrical conductivity (EC) of either saturated soil paste or irrigation water as an important indicator for water quality.…”
Section: Core Ideasmentioning
confidence: 99%